High Sugar and Fat Additives in Fast Food Restaurants: Is Whether Addiction or Consumer Loyalty? - Herlin Widasiwi Setianingrum; Martinus Tukiran (Jurnal Penelitian Pendidikan IPA, 2024)
The article will describe how chemicals in fast food and consumer loyalty to consume in high frequency. The chemical reality of fast food is suspected to cause addiction so that on the other hand consumers will appear loyal. This research applies a systematic review to examine studies exploring customer loyalty in the context of fast-food restaurants. The systematic review was chosen as the most appropriate method because its aim is to collect, critically evaluate, integrate, and present findings from various research studies relevant to the research question or topic. The findings offer significant theoretical implications for future research in this field and practical implications for practitioners in the fast-food industry. The initial relevance of each manuscript was determined based on its title. Manuscripts that appeared to discuss customer loyalty within the fast-food industry were selected for further evaluation. This study collected comprehensive information from these selected studies, including the author, year, title, and abstract. It’s noteworthy that all references utilized in this study are derived exclusively from English-language literature. The research contributes to the existing literature by providing a comprehensive and updated summary of the antecedents and their effects, and it offers actionable insights and recommendations on how to enhance customer loyalty, thereby providing a competitive advantage in the fast-food industry.